2020
DOI: 10.1001/jama.2020.5230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Doxycycline on Aneurysm Growth Among Patients With Small Infrarenal Abdominal Aortic Aneurysms

Abstract: OBJECTIVE To test whether doxycycline reduces the growth of abdominal aortic aneurysm over 2 years as measured by maximum transverse diameter. DESIGN, SETTING, AND PARTICIPANTS Parallel, 2-group, randomized clinical trial that was conducted at 22 US clinical centers between May 2013 and January 2017, and enrolled patients 50 years or older with small (3.5-5.0 cm for men, 3.5-4.5 cm for women) infrarenal aneurysms. The final date of follow-up was July 31, 2018.INTERVENTIONS Patients were randomized to receive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 38 publications
2
81
0
1
Order By: Relevance
“…There have been a few drug classes that have gone into clinical trials such as doxycycline, angiotensin-converting enzyme (ACE) inhibitors, and a few studies evaluating statins. However, conclusive evidence suggesting effective reduction in size or growth rate has yet to be reported, though some trials are still ongoing [ 10 , 11 , 12 ]. Moreover, therapeutic advancement would positively affect surgery and stenting application [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few drug classes that have gone into clinical trials such as doxycycline, angiotensin-converting enzyme (ACE) inhibitors, and a few studies evaluating statins. However, conclusive evidence suggesting effective reduction in size or growth rate has yet to be reported, though some trials are still ongoing [ 10 , 11 , 12 ]. Moreover, therapeutic advancement would positively affect surgery and stenting application [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to the successes in preclinical studies, the Pharmaceutical Aneurysm Stabilization Trial (PHAST) trial found no effect after 18 months of doxycycline treatment (100 mg/day) [ 66 ]. This was confirmed by a recently published randomized clinical trial by Baxter et al (Non-Invasive Treatment of Abdominal Aortic Aneurysm Clinical Trial (N-TA 3 CT)), reporting that doxycycline (200 mg/day) did not reduce AAA growth at 2 years as compared to placebo in patients with small infrarenal AAA [ 67 ]. While it was previously argued that the doxycycline dose used in the PHAST trial was too low to have an effect on AAA, the dose in the N-TA 3 CT trial corresponded to circulating levels of doxycycline that were required to reduce AAA growth in preclinical studies with mice [ 67 ].…”
Section: The Role Of the Extracellular Matrix In Aaamentioning
confidence: 81%
“…This was confirmed by a recently published randomized clinical trial by Baxter et al (Non-Invasive Treatment of Abdominal Aortic Aneurysm Clinical Trial (N-TA 3 CT)), reporting that doxycycline (200 mg/day) did not reduce AAA growth at 2 years as compared to placebo in patients with small infrarenal AAA [ 67 ]. While it was previously argued that the doxycycline dose used in the PHAST trial was too low to have an effect on AAA, the dose in the N-TA 3 CT trial corresponded to circulating levels of doxycycline that were required to reduce AAA growth in preclinical studies with mice [ 67 ]. The promising results of the preclinical studies could therefore not be confirmed in human clinical trials.…”
Section: The Role Of the Extracellular Matrix In Aaamentioning
confidence: 81%
“…Favourable clinical outcomes have also been observed with tetracyclines in indications like rheumatoid arthritis, osteoarthritis, Fragile X syndrome, etc. [129,131,[297][298][299][300][301][302][303][304]. A comprehensive summary of pleiotropic non-antibacterial actions and on-going clinical trials was published in 2010 [11] listing 54 and 88 clinical trials for minocycline and doxycycline, respectively, in indications like e.g.…”
Section: Tetracyclinesmentioning
confidence: 99%